2012
DOI: 10.1053/j.sempedsurg.2012.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Hirschsprung-associated enterocolitis: prevention and therapy

Abstract: Hirschsprung-associated enterocolitis (HAEC) remains the greatest cause of morbidity and mortality in children with Hirschsprung disease. This chapter details the various approaches used to treat and prevent this disease process. This includes prevention of complications such as stricture formation, prophylaxis with rectal washouts and identification of high risk individuals. The chapter also details approaches to diagnose HAEC as well as to exclude other etiologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
1
18

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(144 citation statements)
references
References 70 publications
6
112
1
18
Order By: Relevance
“…En caso de establecer diagnóstico de enterocolitis, debe agregarse al tratamiento médico metronidazol vía oral a dosis convencionales y, dependiendo de la gravedad, requerirá ampliación del esquema antibiótico (ampicilina y gentamicina) referido por literatura anglosajona, ayuno, apoyo de soluciones parenterales y vigilancia intrahospitalaria hasta la resolución de la enterocolitis. 2,18 Al realizar ileostomías, la complicación observada más frecuentemente es el prolapso, el cual puede complicarse con isquemia; se recomienda fijar el intestino a la pared abdominal anterior El algoritmo aquí planteado es una sugerencia del autor de acuerdo a su experiencia. *Cuando las condiciones generales del paciente permitan esperar un estudio histopatológico y se cuente con el apoyo de un patólogo puede enviarse una biopsia de espesor total del sitio probable de derivación intestinal y valorar la presencia de células ganglionares.…”
Section: Complicacionesunclassified
“…En caso de establecer diagnóstico de enterocolitis, debe agregarse al tratamiento médico metronidazol vía oral a dosis convencionales y, dependiendo de la gravedad, requerirá ampliación del esquema antibiótico (ampicilina y gentamicina) referido por literatura anglosajona, ayuno, apoyo de soluciones parenterales y vigilancia intrahospitalaria hasta la resolución de la enterocolitis. 2,18 Al realizar ileostomías, la complicación observada más frecuentemente es el prolapso, el cual puede complicarse con isquemia; se recomienda fijar el intestino a la pared abdominal anterior El algoritmo aquí planteado es una sugerencia del autor de acuerdo a su experiencia. *Cuando las condiciones generales del paciente permitan esperar un estudio histopatológico y se cuente con el apoyo de un patólogo puede enviarse una biopsia de espesor total del sitio probable de derivación intestinal y valorar la presencia de células ganglionares.…”
Section: Complicacionesunclassified
“…В настоящее время энтероколит обуслов-ливает до 50% случаев летальных исходов от болезни Гиршпрунга [4]. Несмотря на разнообразие рассматри-ваемых в научной литературе этиологий болезни, био-логические механизмы, лежащие в ее основе, изучены недостаточно [5].…”
Section: обоснованиеunclassified
“…Микробная роль в развитии энтероколита «подозревалась» давно и впер-вые была описана более 50 лет назад. Так, C. difficile может, хотя и не во всех случаях, являться возбудителем энтероколита [5].…”
Section: обоснованиеunclassified
See 1 more Smart Citation
“…Hirschsprung-associated enterocolitis is the most common Clinical Microbiology: Open Access complication in HD patients and it represents the greatest cause of morbidity and mortality in children with HD. Despite many proposed etiologies, the exact mechanisms underlying HAEC are still poorly understood [14]. Several studies have shown that not only the increase of Clostridium difficile and Rotavirus, but also a reduction in Bifidobacteria and Lactobacillus may play a role in the pathogenesis of HAEC [15].…”
Section: Editorialmentioning
confidence: 99%